Thomas Crown affair - Brosnan, Pierce; St. Clair, Beau.; Trustman, Alan.; Dixon, Leslie; Wimmer, Kurt, 1964-; McTiernan, John.; Russo, Rene.; Leary, Denis; Conti, Bill.; Metro-Goldwyn-Mayer.; Irish Dreamtime (Firm); Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, Calif. Distributed by 20th Century Fox Home Entertainment, 2010)
Thrill-seeking billionaire Thomas Crown pulls off the ultimate heist when he steals a priceless painting from a Manhattan museum - stealing it in broad daylight. But when he finds himself up against the beautiful insurance investigator hired to retrieve the masterpiece, the two engage in the most dangerous and intoxicating game of cat-and-mouse either has ever experienced.
Title from container.
Originally released as a motion picture in 1999.
Special features: Disc two: Full-length film in both widescreen (Side A) and full screen (Side B) presentations; audio commentary by director John McTiernan.
Director of photography, Tom Priestley ; editor, John Wright ; music, Bill Conti.
Pierce Brosnan, Rene Russo, Denis Leary.
MPAA rating: R; for some sexuality and language.
Keywords: Art thieves -- New York (State) -- New York -- Drama; Painting -- New York (State) -- New York -- Drama; Insurance investigators -- New York (State) -- New York -- Drama; Criminal behavior -- New York (State) -- New York -- Drama; Man-woman relationships -- New York (State) -- New York -- Drama; New York (State) -- New York; Action and adventure films; Drama; Feature films; Thrillers (Motion pictures); Video recordings for the hearing impaired